2019
DOI: 10.1029/2019ja026583
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Drag Measurements of Aluminum Particles in Free Molecular Flow

Abstract: High‐speed drag in a free molecular flow is still poorly understood despite playing an important role in a variety of physical situations, including meteor ablation in the upper atmosphere, the orbits of satellites, and the dynamics of cosmic dust grains. To measure drag at high speeds, small aluminum spheres 0.1–2.1 μm in radius were shot at 1–10 km/s into air, N2, Ar, and CO2 using an electrostatic dust accelerator. The measured drag coefficient in air is Γ = 1.29 ± 0.13, with similar values for the other ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Figure 4 shows an example of an observed event compared to the model using these parameters. The best‐fit heating coefficient is consistent with the results of DeLuca and Sternovsky (2019), who found that the heating coefficient can be less than 1. Using Equation (), the best‐fit heating coefficient corresponds to a drag coefficient Γ = 1.24 , which is very similar to the drag coefficients measured by DeLuca and Sternovsky (2019).…”
Section: Ppy Ablation Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 4 shows an example of an observed event compared to the model using these parameters. The best‐fit heating coefficient is consistent with the results of DeLuca and Sternovsky (2019), who found that the heating coefficient can be less than 1. Using Equation (), the best‐fit heating coefficient corresponds to a drag coefficient Γ = 1.24 , which is very similar to the drag coefficients measured by DeLuca and Sternovsky (2019).…”
Section: Ppy Ablation Modelsupporting
confidence: 89%
“…(2013), who found organic coatings of approximately 100 nm thickness on the individual submicron grains that form micron‐size aggregate particles. The particle entered the atmosphere at an angle of 0° to the zenith, and the heating coefficient was set to Λ = 0.6 , which was the heating coefficient found by DeLuca and Sternovsky (2019). The ablating particle deposited its entire PPy content into the atmosphere over a relatively narrow altitude range of 93–94 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briani et al (2013) calculate the Λ as an output of their numerical model (0.9 for low velocities), and Popova et al (2007) calculates Λ with energy ratios from Monte Carlo simulations, finding Λ between 0.75 and 1.0. Experimentally, DeLuca and Sternovsky (2019) used a measured drag coefficient to constrain the energy transfer coefficient to Λ = 0.58 ± 0.37 for a low velocity aluminum target in air. MD simulations with physical interatomic potentials can provide an estimate for the energy transfer coefficient as well, and this is the subject of the paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, the single particle impacts influence the heating rate of the meteoroid, which determines the thermal mass loss rate as well. Thermal ablation is sometimes referred to as evaporation (Briani et al, 2013;Campbell-Brown & Koschny, 2004;Čapek & Borovička, 2017;Čapek et al, 2019;Ceplecha et al, 1998;Girin, 2017;Popova, 2004) or thermal mass loss (DeLuca & Sternovsky, 2019;Hill et al, 2004;Rogers et al, 2005;Thomas, 2017;Vondrak et al, 2008). We have chosen to use the term thermal ablation as it encapsulates all possible phase transitions due to the thermal energy imparted on the meteoroids surface from atmospheric particles.…”
Section: Introductionmentioning
confidence: 99%